Development Of Cutting Tools Design Simplicia Turmeric By Using TRIZ Method - Dendra Febriawan; Rahmaniyah Dwi Astuti; Ilham Priadythama (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
To increase the production of simplicia, has been designed and fabricated rhizome cutting tools with 5 parallel blades. Based on testing, there were still weaknesses known in the knife-blade thus inhibiting the cutting process. At the beginning of the research showed that the bottleneck caused by the cutting blade is too thick to be a narrow gap between the blade and the friction becomes large rhizome pieces. Thinning of the blade is not necessarily done because it will weaken the blades. This research aims to provide design solutions that is able to overcome a problem of the blade is. To obtain a solution to the existing contradiction problems, TRIZ method was used. The first step taken is identification the problem include the study of literature and direct observations of turmeric rhizome cutting tools. Then followed by determining technical requirements of design, resolve problems that occur contradiction, the last is preparation of design concept and the determination of the design specifications. The results of this research is produce design concept and resolve most issues contradictions mainly on cutting blades. By using TRIZ method, the design of cutting blades not occurring deflection, because the shape of blade was thin and there was additional features that serve to regulate the tension of cutting blades.